Job Satisfaction Analysis: Burnout, Stress, Work Life Balance - Evi Silvana Muchsinati; Diah Mulia Sari; Dessy Aliandrina (Goodwood Publishing, 2026)
Purpose: This study explores the influence of job burnout, stress, and work-life balance on job satisfaction among government employees and whether organizational support moderates these effects. Research Methodology: This study was conducted with the Provincial Government of the Riau Islands, using a structured questionnaire completed by 363 civil servants. A non-probability sampling method was applied because of limited time and access. The data were processed using SEM-PLS, which is ideal for non-normal and complex data models. Results: The analysis revealed that burnout and work-life balance have a significant influence on job satisfaction. In contrast, job stress was found to have a negligible effect. The expected moderating effect of organizational support did not show a significant statistical influence on the relationships between the variables. Conclusions: Efforts to reduce burnout and promote a healthy work-life balance appear to be effective ways to improve job satisfaction among public employees. Organizational support does not alter the strength of these relationships. Limitations: The generalizability of the results is limited by the use of a non-random sample and focus on one regional public institution. Contributions: This study adds value to public sector HR research by offering insights for policymakers and managers to enhance employee satisfaction through better workload management and work-life integration strategies.